Improved synthesis of N-heterocyclic olefins and evaluation of their donor strengths. (29th March 2016) - Powers, Kate; Hering-Junghans, Christian; McDonald, Robert; Ferguson, Michael J.; Rivard, Eric
Graphical abstract: An efficient synthetic route to N -heterocyclic olefins (NHOs) is described. NHOs bind to rhodium carbonyls and these complexes were used to determine the binding mode and donor properties of this emerging ligand class. Abstract: An improved synthesis of N -heterocyclic olefins (NHOs) containing terminal CH2 donor groups was developed. A preliminary investigation of the bonding mode and donor strengths of various structurally distinct NHOs was conducted by analysis of the IR and NMR spectra of their corresponding rhodium carbonyl complexes NHO·RhCl(CO)2, along with examination of pertinent metrical parameters via X-ray crystallography and Density Functional Theory (DFT) computations.